The Contribution of Push Up and Pull Up Exercises to the Strength of 2-Point Shooting Throws in Basketball Players of Bintang Muda Club in Kendal District - Ricky Darmawan; Ipang Setiawan (Universitas Negeri Semarang, 2025)
The aim of this research is to determine how push-up and pull-up exercises contribute to the strength of 2-point shooting throws among players of the Bintang Muda Basketball Club in Kendal District. Weak arm muscle strength, which affects the accuracy and power of 2-point shots, is the main issue addressed in this research. This study uses a quantitative approach with a pretest-posttest experimental design and no control group. A sample of 20 individuals was used in this study. Data was collected through observation and measurement of 2-point shooting ability, and then analyzed using the Pearson Product Moment correlation test. The results showed that push-up and pull-up exercises had a significant impact and contributed meaningfully to the strength of the arm muscles and accuracy of 2-point shots for the players. A strong and significant relationship was found between the type of exercise and 2-point shooting strength, indicated by a correlation coefficient of 0.542 and a significance value of 0.014 (< 0.05). Therefore, push-up and pull-up exercises have a significant contribution to 2-point shooting strength in basketball and can be considered part of a physical training program to improve 2-point shooting techniques in basketball games.